' … and now it's over to you': recognising and supporting the role of careers leaders in schools in England. Issue 2 (15th March 2017) - Andrews, David; Hooley, Tristram
ABSTRACT: There is a long history of teachers and schools being involved in the delivery of career education and guidance. As the breadth of career education and guidance activity in English schools grew throughout the twentieth century it became increasingly necessary to have an individual within the school responsible for leading and managing this activity (the careers leader). The transfer of responsibility for career guidance from local authorities to schools following the Education Act 2011 has intensified the need for this role. There have been various attempts to conceptualise and professionalise the role of careers leader and to develop appropriate training and support. This article defines the role and the rationale for the role, sets out its history and makes recommendations for the future professionalisation of the role. It is argued that this will include recognition of the role by policy, professionalisation and the development of a career structure and the development of appropriate training and CPD.